2009
DOI: 10.1002/ptr.2975
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of vanillin and its effects on mechanical hypersensitivity in a rat model of neuropathic pain

Abstract: The analgesic effects of vanillin on neuropathic pain was evaluated using thermal sensitivity and mechanical allodynia using the sciatic nerve constriction model (n = 30 rats). To determine the pharmacokinetics of vanillin, rats (n = 6/administration route) received either 20 or 100 mg/kg of vanillin i.v. and p.o., respectively. For the pharmacodynamic study, baseline levels for hyperalgesia and allodynia were taken for 5 days prior to surgery. Following surgery each group (n = 6 rats/group) received either va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
45
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 38 publications
6
45
2
1
Order By: Relevance
“…Compared to our previous results where the reaction time on the Hargreaves decreased to 5 sec in neuropathic animal with the sciatic nerve ligation model, the animals with the caudoputamenthalamus lesions had a longer reaction time (7-9 sec) following the 2 µL collagenase solution injection which suggests that the pain is not as severe in these animals (Guenette et al, 2007;Beaudry et al, 2010). However with the 3 µL collagenase injection, pain threshold were similar to the animals with sciatic nerve injury.…”
Section: Discussioncontrasting
confidence: 63%
“…Compared to our previous results where the reaction time on the Hargreaves decreased to 5 sec in neuropathic animal with the sciatic nerve ligation model, the animals with the caudoputamenthalamus lesions had a longer reaction time (7-9 sec) following the 2 µL collagenase solution injection which suggests that the pain is not as severe in these animals (Guenette et al, 2007;Beaudry et al, 2010). However with the 3 µL collagenase injection, pain threshold were similar to the animals with sciatic nerve injury.…”
Section: Discussioncontrasting
confidence: 63%
“…Pharmacokinetics of vanillin. Studies in rats have shown that orally administered vanillin (100 mg/kg) is absorbed in the gastrointestinal tract and reaches a ;3 mM peak plasma concentration 4 hours after administration (Beaudry et al, 2010), suggesting poor uptake, rapid clearance, and/or excessive metabolism as has been described for curcumin (section III.A and Fig. 11).…”
Section: B Pharmacokinetics and Pharmacodynamics Of Curcumin Catabolmentioning
confidence: 90%
“…11). Intravenously administered vanillin is almost completely cleared or metabolized within 2 hours (Beaudry et al, 2010). Correspondingly, analysis of urine retrieved from rats 24 hours after an oral dose of vanillin (100 mg/kg) revealed that vanillin is extensively cleared via the renal system in conjugated form, mainly as vanillin glucuronide and sulfate (Kirwin and Galvin, 1993).…”
Section: B Pharmacokinetics and Pharmacodynamics Of Curcumin Catabolmentioning
confidence: 99%
“…4). One of the limitations of using o-vanillin in vivo is its poor bioavailability, as has been reported previously for its isomer, vanillin (40). Due to this challenge, we administered a high dose twice to achieve an appreciable inhibitory effect in vivo.…”
Section: C29 Blocks Tlr2 Bacterial Agonist-induced Proinflammatory Genementioning
confidence: 98%